PROTEIN PHOSPHATASE 1В IN THE PATHOGENESIS OF LARYNGEAL AND HYPOPHARYNGEAL CANCER - G. V. Kakurina; D. E. Kulbakin; O. V. Cheremisina; I. V. Kondakova; E. L. Choynzonov (Сибирский онкологический журнал, 2017)
To predict the development and clinical course of squamous cell head and neck carcinoma (SCHNC), we studied the level of protein phosphatase 1B (РРМ1В) using the proteomic analysis. Verification of the results of proteomic analysis by ELISA showed that the level of РРМ1В in blood serum of patients with SCHNC depended on the disease stage. The level of РРМ1В in the blood serum of patients with stage T1N0M0 cancer was higher than that observed in the control group and in patients with chronic hyperplastic laryngitis. In tumor tissue, the level of РРМ1В was associated with the size of the primary tumor and the presence of metastases. In tumor tissue, the level of РРМ1В was also higher in patients with stage T1N0M0 than in patients with chronic hyperplastic laryngitis. The data obtained indicate that the level of РРМ1В can be used for early detection and prediction of the clinical course of SCHNC. Further studies with larger cohorts of patients are required to evaluate the prognostic significance of the РРМ1В level.